UPAYA MENINGKATKAN MINAT BELAJAR WUDHU MELALUI METODE DEMONTRASI PADA SISWA KELAS IV SDN 14 SITIUNG - Sabli Sabli (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2020)
Interest in a learning process is a student's tendency to observe, feel, and involve in learning activities accompanied by pleasure. Interest has a very big influence in the learning process, because if the subject taught is not in accordance with student interests, students tend not to learn well because of the lack of attraction coming from the students themselves. This research was clasified as classroom action research (CAR) through two cycles. Each cycle consists of four stages, namely: designing, implementing, observing, and reflecting. Subjects of this research were the fourth grade students of SDN 14 Sitiung. Data obtained of this research was observation sheets on learning process. Results of the analysis shows that students’ learning outcomes increase from pre-cycle, cycle I to cycle II, namely, pre-cycle (48%), cycle I (63%), and cycle II (86%). It can be said that the demonstration method can increase the students’ learning interest at SDN 14 Sitiung in academic year 2019/2020, so that this method can be used as an alternative to learning Islamic Religious Education in Elementary School.